Examining social exchange measures as moderators of politeness techniques in face-threatening acts between romantic partners - Allred, Ryan J., author; Crowley, John P., advisor; Aoki, Eric, committee member; Lucas-Thompson, Rachel, committee member (Colorado State University. Libraries, 2016)
Much has been written concerning face and the process individuals engage in to manage both their own and other’s face in a variety of contexts (Goffman, 1967). Despite ample research on the management of one’s own face (Brown & Levinson, 1987), still little is known concerning the motives behind helping others to create and manage face. This study utilizes measures from Social Exchange Theory (Thibaut & Kelley, 1959) as moderators for face-saving techniques presented in Politeness Theory. Particularly, romantic relationships were examined to determine how relationship satisfaction and stability levels influence decision-making processes when individuals approach their partners with a face-threatening act. Satisfaction was shown to be associated with concern for face whereas stability, commitment, and equity were not. Additionally, satisfaction and stability levels are correlated with the techniques individuals use to reduce uncertainty concerning their partners’ face needs. Future research is suggested to further understand effective techniques to reduce uncertainty surrounding face-threatening acts.
Keywords: facework; satisfaction; face; social exchange; politeness